Commodity Markets Outlook, April 2015 - World Bank Group (Washington, DC, 2015)
The decline in commodity prices that began with metals and agriculture four years ago—joined by crude oil in mid-2014—continued in 2015Q1 (Figure 1). Energy, metals, and agricultural prices were down 28, 11, and 5 percent, respectively, from the previous quarter. Increasing supplies, bumper harvests, weak demand and a stronger U.S. dollar contributed to the declines. The weakness is expected to continue for the rest of the year. All key price indices are projected to decline in 2015 before recovering moderately in 2016 (Figure 2). This issue’s Special Focus section examines the four episodes of oil price crashes since 1970 and finds that the 2014-15 and 1985-86 crashes were driven mostly by supply-related factors, while the other two episodes were associated with the First Gulf War and 2008 financial crisis, respectively. This report is released quarterly, in January, April, July, and October. It provides detailed market analysis for major commodity groups, including energy, metals, agriculture, precious metals, and fertilizers. Price forecasts to 2025 for 46 commodities are also presented, together with historical price data.